2015
DOI: 10.18632/oncotarget.5828
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of metastatic disease in the brain in relation to the hippocampus: a retrospective single-center analysis of 6064 metastases in 632 patients

Abstract: This study aimed to investigate the patterns of brain metastasis and to explore the risk factors affecting hippocampus metastasis (HM). We retrospectively analyzed the clinical information of patients with metastatic disease in the brain. The associations between clinicopathologic variables with HM and peri-hippocampal metastasis (PHM) were evaluated in univariate and multivariate regression analyses. A total of 632 patients with 6064 metastatic lesions were recruited into the present study. Of these, 4.1% (26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
3
22
1
Order By: Relevance
“…In this study, we identified patients from two cancer centers, and the probabilities of HM (3.6%) and PHM (7.3%) were not significantly higher than the previous results (4.1% of patients developed HM and 5.5% of patients developed PHM in our previous study) 11. In a previous study of 314 Chinese patients, the percentages of HM and PHM were 4.1% and 11.1%, respectively 10.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In this study, we identified patients from two cancer centers, and the probabilities of HM (3.6%) and PHM (7.3%) were not significantly higher than the previous results (4.1% of patients developed HM and 5.5% of patients developed PHM in our previous study) 11. In a previous study of 314 Chinese patients, the percentages of HM and PHM were 4.1% and 11.1%, respectively 10.…”
Section: Discussionmentioning
confidence: 50%
“…Our previous single center study of 56 breast cancer patients observed an increase in risk of PHM relative to patients with other types of cancers, although the association was not statistically significant ( P =0.084) 11. In this study, we identified patients from two cancer centers, and the probabilities of HM (3.6%) and PHM (7.3%) were not significantly higher than the previous results (4.1% of patients developed HM and 5.5% of patients developed PHM in our previous study) 11.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of the RTOG 0933 trial showed that the decrease of the neurocognitive function from baseline to 4 months in the HS-WBRT group was significantly lower than that in the historical control group (7.0% vs 30.0%, P  < .001) [15]. Despite the potential to disseminate to the brain, the incidence of HMs and PHMs in patients with SCLC is not significantly higher than other malignant tumors [18], [19], [20], [24], [25]. Therefore, HS-WBRT in patients with SCLC is also feasible.…”
Section: Discussionmentioning
confidence: 92%
“…Cerebellar metastases make up approximately 18% of BM. The least common area is the brainstem [26,29,30]. Studies have suggested that the sites of BMs vary based on the primary site of origin and cerebral blood flow.…”
Section: Clinical Presentationmentioning
confidence: 99%